A scoping review of lifestyle and behavioral treatment approaches for binge eating disorder - Wang, Debby (Kansas State University, 2022)
Binge eating disorder (BED) significantly impacts quality of life. The Diagnostic and Statistical Manual of Mental Disorders, 5th ed. (DSM-V) published May 18, 2013, was revised to include BED as a distinct diagnosis. The aim of this review was to map the research on lifestyle and behavioral treatments for BED since the diagnostic change. Population characteristics were assessed to evaluate features within studies and whether disparities exist. Three databases (PubMed, PsycInfo, and Scopus) were searched for relevant articles. Eleven studies were identified for review. Four studies were pilot/proof of concept (POC) studies, five included some form of self-help intervention strategy, and two were group therapies. Studies included new treatment approaches and adaptations for wider dissemination. Only one study investigated a multidisciplinary approach and one on stepped care. Studies indicated that compassion-based therapies are promising for treating BED. All self-help therapies significantly reduced binge eating frequency. Self-help treatments were based on Cognitive Behavioral Therapy (CBT), Dialectical Behavioral Therapy (DBT), and self-esteem focused CBT. Integrative Cognitive-Affective Therapy (ICAT BED) was found to be comparable to guided self-help CBT. There is limited support for group treatment focused on associated BED factors (impulsivity, negative affect, and low activation). Lack of diversity in participants continue to be an issue with majority female Caucasian participants. Inconsistency found between studies in types of demographics reported and how each was measured. Outcome measures and exclusion criteria between studies varied widely. None of the studies reviewed used the added severity rating in the DSM-V criteria in participant selection.
Keywords: Eating disorder; Binge eating disorder; Scoping review